Grammar Peculiarities of Scientific and Technical Translation in Construction Sphere - Ageicheva, Anna; Hunchenko, Yuliia (International Journal of Engineering and Technology, 2018)
Constant progress in the world construction sphere which includes innovation technologies implementation and intense business development can be observed during the recent years. All these result in the widening construction concept framework, leading to enrichment of English construction terminological system, which in turn causes huge linguists’ interest to terminology, as well as intensifies research in scientific and technical translation sphere.Construction terminology occupies a special place among other terminologies due to specificity of the human activity sphere it supplies. In the context of construction terminology the domain specific terminologies are marked out, among them the terminologies of building machinery, construction materials, mathematics, physics, chemistry, electrical engineering, town-planning, ecology, etc. Diversified study in the field of modern English construction terminology and special aspects of its translation contributes to identification of its formation regularity, functioning, systematization, and helps to predict the main tendencies of its further development. This is what determines the field of our research.